The reason/emotion dualism in Western political thought and psychiatric practice - Serafimov, Alex (2020)
This thesis examines whether Western psychiatric practices reflect how the relationship between reason and emotion has been conceptualised in Western political thought. It also investigates whether Western political conceptions of the relationship between reason and emotion can be used to criticise these psychiatric practices, and whether these psychiatric practices harm patients’ ability or willingness to partake in political action. It does this by looking at two case studies, the lobotomy procedure and Cognitive Behavioural Therapy (CBT), before discussing how a dozen Western political thinkers have conceptualised the relationship between reason and emotion. These thinkers are Plato, Aristotle, Seneca, Epictetus, Augustine, Thomas Hobbes, David Hume, Jean-Jacques Rousseau, Friedrich Nietzsche, Sigmund Freud, Michel Foucault, and Martha Nussbaum. In this way, this thesis politicises psychiatric practices and engages mental health professionals and political theorists in an overdue discussion between their fields.